The future of the Malay Language - Ungku Abdul Aziz, Ungku Abdul Hamid
There is always a turning point for a language to become a popular language in the international society. Once Malay was the language of a great empire. However, Western Imperialism has destroyed the unity and the influence of the Malay language. The Malay scholars had suppressed the Malay language further for their imperialism without considering the consequences to the culture and the society. After the declaration of independence, it was the first time Malay language has been used throughout the administration and universities. New concepts and new styles were introduced into the language and the spelling system was reformed and systematic development of technical vocabularies became widely discussed issues. Congresses were organized in both Malaya and Indonesia to build up and develop the language. Today the Malay language has been made the national language to unify all the people in Malaya. The Malay language which has survived the 400 years of dark age, is likely to evolve in the soon future. By the end of 20th century, Western historians will treat the study of Malay culture and language as a continuous cycle of progress with a brief interruption during a dark age. By then Malay will have been accorded its rightful place in the history of civilization.